New Daily Persistent Headache in a Pediatric Population. (September 2021) - Strong, Eric; Pierce, Emily Linda; Langdon, Raquel; Strelzik, Jeffery; McClintock, William; Cameron, Mark; Furda, Mary; DiSabella, Marc
Introduction: New daily persistent headache (NDPH) is a primary headache disorder characterized by an intractable, daily, and unremitting headache lasting for at least 3 months. Currently, there are limited studies in the pediatric population describing the characteristics of NDPH. Objective: The objective of the current study is to describe the characteristics of NDPH in pediatric patients presenting to a headache program at a tertiary referral center. Methods: The participants in the current study were pediatric patients who attended the Headache Clinic at Children's National Hospital between 2016 and 2018. All patients seen in the Headache Clinic were enrolled in an institutional review board–approved patient registry. Results: Between 2016 and 2018, NDPH was diagnosed in 245 patients, representing 14% of the total headache population. NDPH patients were predominantly female (78%) and white (72%). The median age was 14.8 years. The median pain intensity was 6 of 10 (standard deviation = 1.52). Most patients reported experiencing migrainous features, namely, photophobia (85%), phonophobia (85%), and a reduced activity level (88%). Overall, 33% of patients had failed at least 1 preventive medication, and 56% had failed at least 1 abortive medication. Furthermore, 36% of patients were additionally diagnosed with medication overuse headache. Conclusion: NDPH is a relatively frequent disorder among pediatric chronic headache patients. The vast majority of these patients experience migrainous headache characteristics and associated symptoms and are highly refractory to treatment—as evidenced by a strong predisposition to medication overuse headache and high rates of failed preventive management.